Preliminary list of Cossidae sensu str. (Lepidoptera, Cossoidea: Cossidae: Cossinae & Zeuzerinae) of the Republic of Angola with description of a new Strigocossus species - Yakovlev, Roman V.; Sulak, Harald; Witt, Thomas J. (Zootaxa, 2019)
An annotated list of the Cossidae of the Republic of Angola, including 24 species from 12 genera in two subfamilies, is presented. Thirteen species of Cossidae are reported for the first time from Angola. Strigocossus otti is described as a new species, sp. nov.